Emergenza COVID-19: dati, standard ed interoperabilití o solo dashboard? - Cesare Gerbino (GEOmedia, 2020)
With the COVID pandemic, we witnessed the proliferation of dashboards used to communicate the information and data of the spread of the infection by the public administrations that hold this information. Similar efforts have not been made to publish the data on which these dashboards are based in an open and interoperable way. The article aims to make a (non-exhaustive) picture of the Italian context from which a situation emerges with ample room for improvement from this point of view and offers some opportunities, in terms of standards and ways in which the purpose of making this information open in order to allow anyone who wants to deepen or cross them to operate on such data, creating added value and helping to understand this epochal event.